1997
DOI: 10.37236/1296
|View full text |Cite
|
Sign up to set email alerts
|

On Random Greedy Triangle Packing

Abstract: The behaviour of the random greedy algorithm for constructing a maximal packing of edge-disjoint triangles on $n$ points (a maximal partial triple system) is analysed with particular emphasis on the final number of unused edges. It is shown that this number is at most $n^{7/4+o(1)}$, "halfway" from the previous best-known upper bound $o(n^2)$ to the conjectured value $n^{3/2+o(1)}$. The more general problem of random greedy packing in hypergraphs is also considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…Recently Bohman, Frieze and Lubetzky have shown that the random triangle‐removal process terminates a.a.s. with n3/2+o(1) edges improving previous results by Spencer , Rödl and Thoma and Grable .…”
Section: Introductionsupporting
confidence: 81%
“…Recently Bohman, Frieze and Lubetzky have shown that the random triangle‐removal process terminates a.a.s. with n3/2+o(1) edges improving previous results by Spencer , Rödl and Thoma and Grable .…”
Section: Introductionsupporting
confidence: 81%
“…This is in fact the case: It was shown by Spencer [9] and independently by Rödl and Thoma [7] that |E(M)| = o(n 2 ) with high probability 1 . This was extended to |E(M)| ≤ n 11/6+o (1) by Grable in [6], where the author further sketched how similar arguments using more delicate calculations should extend to a bound of n 7/4+o(1) w.h.p. By comparison, it is widely believed that the graph produced by the random greedy triangle-packing process behaves similarly to the Erdős-Rényi random graph with the same edge density, hence the process should end once its number of remaining edges becomes comparable to the number of triangles in the corresponding Erdős-Rényi random graph.…”
Section: Introductionmentioning
confidence: 92%
“…and the stopping time T j is the minimum of max{j, T } and the smallest index i ≥ j such that Q(i) is not in the critical interval (6). (Note that if Q(j) is not in the critical interval then we have T j = j.)…”
Section: Proof Of Theoremmentioning
confidence: 99%
“…This problem attracted much attention (see e.g. [15,29,31]), culminating in a result of Bohman, Frieze and Lubetzky [3] where the exponent was finally approximately confirmed. We adapt the triangle removal process so that it does not just produce a partial Steiner triple system, but a k-sparse one.…”
Section: Theorem 13 ([24]mentioning
confidence: 99%